2013
DOI: 10.1111/dote.12079
|View full text |Cite
|
Sign up to set email alerts
|

Esophagojejunostomy after total gastrectomy for caustic injuries

Abstract: The objective of the study was to compare outcomes of emergency esophagogastrectomy (EGT) and total gastrectomy with immediate esophagojejunostomy (EJ) in patients with full-thickness caustic necrosis of the stomach and mild esophageal injuries. After caustic ingestion, optimal management of the esophageal remnant following removal of the necrotic stomach remains a matter of debate. Between 1987 and 2012, 26 patients (men 38%, median age 44 years) with isolated transmural gastric necrosis underwent EGT (n = 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Decisively, every effort possible should be made to mature a feeding jejunostomy at the initial operation, to provide enteral feeding and avoid parenteral nutrition, which are known to prolong hospital stay, and increase the risk of infections [ 10 , 11 ]. Although some authors have advocated immediate restoration of the GI tract with esophagojejunostomy, this option should only be used for stable patients with minimal intraperitoneal soiling [ 12 ]. On the contrary, restoration of the GI tract should be performed as soon as the patient has recovered from the systemic insult of the caustic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Decisively, every effort possible should be made to mature a feeding jejunostomy at the initial operation, to provide enteral feeding and avoid parenteral nutrition, which are known to prolong hospital stay, and increase the risk of infections [ 10 , 11 ]. Although some authors have advocated immediate restoration of the GI tract with esophagojejunostomy, this option should only be used for stable patients with minimal intraperitoneal soiling [ 12 ]. On the contrary, restoration of the GI tract should be performed as soon as the patient has recovered from the systemic insult of the caustic injury.…”
Section: Discussionmentioning
confidence: 99%
“…If necrosis is confined to the stomach, total gastrectomy with preservation of the native esophagus or esophageal diversion should be considered [38]. Immediate esophagojejunostomy reconstruction can be performed safely with low leak rates (5–8%) [64]. Partial gastric resections are not recommended because ongoing necrosis might compromise patient survival.…”
Section: Methodsmentioning
confidence: 99%
“…The literature research revealed the need for standardised therapeutic strategies in case of caustic ingestion, particularly since there are no randomised controlled trials and the majority of published data consist of literature reviews and retrospective studies exhibiting a low evidence level 9 18. However, a retrospective analysis indicated that immediate oesophagojejunostomy after total gastrectomy might represent a safe therapeutic option 19. A three-stage surgical procedure including total gastrectomy and concomitant oesophagojejunostomy after caustic ingestion has been reported recently 20.…”
Section: Discussionmentioning
confidence: 99%